Karakteristik Sosial Ekonomi Keluarga Nelayan Desa Muara Telake Kecamatan Long Kali Kabupaten Paser - Hadad Nazrey Johani; Fitriyana Fitriyana; Wahyu Fahrizal (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
The purpose of this study is to analyze the social and economic characteristics of fishing households in Muara Telake Village and to identify the supporting and inhibiting factors affecting fishermen. This research employs a quantitative descriptive method with a descriptive analysis approach and purposive sampling technique, involving 24 respondents. Data were analyzed using percentage techniques to illustrate the overall social and economic conditions of the fishermen. The results indicate that the social condition of fishermen falls into the “moderate” category, with an average percentage of 67.29%, covering indicators such as education, age, number of dependents, and health. Meanwhile, the economic condition is also categorized as “moderate,” with an average percentage of 53.70%, encompassing income, expenditure, housing conditions, and asset ownership. Supporting factors include good health, government assistance, family support, and the fishermen’s experience. Conversely, inhibiting factors include low education levels, unpredictable environmental conditions, limited capital, fluctuating fuel prices, and restricted market access, which affect productivity and the welfare of fishing households. These findings highlight the need for targeted interventions to enhance both social and economic well-being.